2017
DOI: 10.6007/ijarbss/v7-i6/2968
|View full text |Cite
|
Sign up to set email alerts
|

Use of Plastic Money in Zimbabwe, Threats and Opportunities for Rural Communities

Abstract: Since the Zimbabwean economy adopted the US dollar as a major currency in 2009, rural communities have remained marginalized in terms of access to financial products and services. The research study evaluates the use and adoption of plastic money by rural communities in Zimbabwe. A descriptive research design was adopted to assess the use of plastic money by rural financially active citizens in Masvingo Province. Data was collected from a sample of 300 respondents using a self-administered questionnaire and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In response to the liquidity constraint, the Reserve Bank has adopted a series of policy Business and Economic Research ISSN 2162-4860 2020 measures aimed at alleviating cash flow problems, including the importation of liquidity, the promotion of the use of plastic currencies, and cash withdrawal limits (Munyanyi, Diza, & Gumbo, 2017;R.B.Z, 2016a). However, even though the use of cashless payment channels increased in the economy, the demand for cash and households' willingness to use cash continued, since goods and services were much cheaper when purchased with cash as compared to plastic currencies.…”
Section: Current Problems In Zimbabwementioning
confidence: 99%
“…In response to the liquidity constraint, the Reserve Bank has adopted a series of policy Business and Economic Research ISSN 2162-4860 2020 measures aimed at alleviating cash flow problems, including the importation of liquidity, the promotion of the use of plastic currencies, and cash withdrawal limits (Munyanyi, Diza, & Gumbo, 2017;R.B.Z, 2016a). However, even though the use of cashless payment channels increased in the economy, the demand for cash and households' willingness to use cash continued, since goods and services were much cheaper when purchased with cash as compared to plastic currencies.…”
Section: Current Problems In Zimbabwementioning
confidence: 99%
“…The usage of innovative electronic trading devices defend the elderly population from theft and fake cases since such cards in his/her wallet can be used immediately and easily in each transaction. Diza et al (2017) focused on plastic money acceptance among rural communities in Zimbabwe. The communities still prefer cash over plastic money, although they cited "anytime anywhere access as major advantage of plastic money.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Gumbo (2016), the world over has experienced an increase in the use of plastic money as a security measure and an efficient way of conducting transactions. Diza, Munyanyi & Gumbo (2017) and Sanderson (2016) assert that Zimbabwe is no exception as more businesses have also embraced plastic money as the country continues to experience banknote shortages. Dzingire (2018) agrees that Zimbabwe has been facing cash shortages since 2016 and the situation worsened from 2017 to date.…”
Section: Introductionmentioning
confidence: 99%
“…Dzingire (2018) agrees that Zimbabwe has been facing cash shortages since 2016 and the situation worsened from 2017 to date. Diza et al (2017) are of the view that using cash for everyday transactions becomes a challenge if a country has a cash crisis like the one obtaining in Zimbabwe. Contrary to the aforementioned, a study by Kaseke (2012) and Nyakuyedzwa, Mutanga & Siwadi (2014) revealed that the uptake of plastic money technology by Zimbabwean consumers and merchants alike had been slow since the Zimbabwe dollar's inflationary era.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation